Kewenangan ITLOS dalam Menyelesaikan Sengketa Pulau Dokdo Antara Jepang dan Korea Selatan - Ghifari, Mohammad Hirzzi; Herlin, Nadiya Eka Putri; Rabbani, Najma Fauziyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
ITLOS or which is an abbreviation for The International Tribunal for the Law of the Sea is a legal body to adjudicate cases and disputes arising from violations of the contents of the convention. In this case, what will be discussed in this research is the case of the dispute between Japan and South Korea, namely the Dokdo island dispute. Dokdo or Takeshima Island is a group of coral islands located in the easternmost part of South Korea and in the northwestern part of Japan. In general, Dokdo Island consists of two main islands, namely Dongdo and Seodo, which come from Korean. The total area of the two islands is 187,453 meters. If divided by the numbers, Dongdo Island has an area of 73,297 meters and Seodo has an area of 88,674 meters. The dispute between Japan and Korea began when Japan lost the second world war. At that time, Japan was asked to return its colonies, including Dokdo Island. Therefore, in 1950 when the Japanese military occupation ended, South Korea immediately declared it their own territory. Talking about research methods, this research uses normative juridical research methods, where research in the process examines literature materials as primary data. The primary legal material in this research is international legal conventions and agreements, namely UNCLOS.